1992
DOI: 10.1007/bf00334484
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of lateral spine scans using dual energy X-ray absorptiometry

Abstract: Reproducibility of lateral spine dual energy X-ray absorptiometry (LAT DEXA) scans using a Lunar DPX-L scanner was assessed in a cadaveric phantom and in patients. One hundred phantom measurements over 7 months demonstrated a longitudinal stability of 1.7% (coefficient of variation, CV). Additional scans were performed with the phantom rotated by up to 20 degrees in each of the three orthogonal planes to assess the effects of variable patient positioning. Horizontal and vertical rotation of the spine had littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…To increase the sensitivity of DXA it has been suggested that BMD be measured with the patient in the lateral decubitus position [35]. There are several reasons for measuring bone mineral from a lateral projection in the vertebral body.…”
Section: Comparison Of Qct and Dxamentioning
confidence: 99%
“…To increase the sensitivity of DXA it has been suggested that BMD be measured with the patient in the lateral decubitus position [35]. There are several reasons for measuring bone mineral from a lateral projection in the vertebral body.…”
Section: Comparison Of Qct and Dxamentioning
confidence: 99%
“…The in vivo precision was 1.7% for measurements of the lumbar spine, 3.6% for measurements of the femoral neck, 3.3% for measurements of Ward's triangle, and 2.2% for measurements of the femoral trochanter. 16 BMD measurements were expressed in absolute terms as g/cm 2 and as a percentage of the initial value. Osteoporosis was defined as a BMD measurement Ͼ2.5 standard deviations below the mean for a healthy population group ages 20 -40 years.…”
Section: Methodsmentioning
confidence: 99%
“…Their data was compared to 25 case controls matched for age (Ϯ2 years) and years since the menopause (Ϯ5 years), who were selected from a group of healthy volunteers, recruited for longitudinal densitometric assessment and undergoing yearly bone mineral density measurements (Larnach et al, 1992). In the prospective study, 15 of the 25 patients with stage II and III myeloma were re-evaluated after 12 months of follow-up.…”
mentioning
confidence: 99%